Photoactivated adenylyl cyclase (PAC) genes in the agellate Euglena gracilis mutant strains - Ntefidou, Maria; Häder, Donat-Peter (ROYAL SOC CHEMISTRY, 2005)
The unicellular, green flagellate wild-type Euglena gracilis ( strain Z) and its colorless phototaxis-mutant strains as well as the non-photosynthetic close relative, Astasia longa, possess several genes of the photoactivated adenylyl cyclase (PAC) family. The corresponding gene products were found to be responsible for step-up ( but not step-down) photophobic responses as well as both positive and negative phototaxis. The proteins consist of two PAC alpha (M-r 105 kDa) and two PAC beta ( 90 kDa) subunits. While the proteins were first believed all to be located in the paraxonemal body (PAB), confocal microscopy revealed that Astasia longa as well as some of the mutant strains do not contain a PAB. Immunofluorescence using PAC antibodies showed that the PAC proteins are also located along the total length of the flagellum at least in some of the strains. In order to determine if the genes responsible for the PAC proteins in the PAB and flagella are identical, sequences of all PAC proteins were analyzed in the Euglena and Astasia strains studied for PAC protein location. Full sequence analysis using PCR and 3' and 5' RACE indicated a substantial divergence between strains with a homology between strains of between 45 and 100%. Sequence alignment and sequence tree construction for the main functional groups (BLUF domain, which binds FAD, and adenylyl cyclase) showed that the paca and the pac beta gene products form clusters each with some of the mutants being closely related while others show a substantial degree of genetic diversity. The conclusion of these results is that there is a family of very dissimilar PAC proteins located in the PAB and the flagellum where they serve different functions in phototaxis and step-up photophobic reactions.